Factors Affecting Residual Stump Length Following Endovenous Laser Ablation. (May 2023) - Pasenidou, Ketino; Tang, Tjun Y.; Juszczak, Maciej; Tiwari, Alok
Background: Current instruction for endovenous laser ablation (EVLA) recommends that the laser fibre tip should be at least 2 cm caudal to the saphenofemoral or saphenopopliteal junction. This is to reduce risk of deep vein thrombosis (DVT) whilst ensuring that the Great Saphenous Vein (GSV)/Short saphenous vein (SSV) occlusion (residual stump) is close to the SFJ/SPJ to reduce recurrence rates. Our aim was to primarily assess the effects of pre-operative junction distance of the laser fibre on stump length but also look at other factors affecting this. Patient and Methods: This was a retrospective analysis of an electronic collected database performing EVLA of the GSV and SSV under local anaesthesia. Patients with previous venous thromboembolic events and incomplete data were excluded. Patients were reviewed at 6 weeks with venous Duplex scan to assess for the residual stump distance and DVT. Multivariable logistic regression was used to account for confounders. Results: Between 2012 and 2018, 2341 patients underwent EVLA and complete data were available on 825 (35.2%) patients. All patients were scanned 6 weeks after procedure. Sixty-nine patients (8.4%) had flush occlusion, 3 patients (.4%) had extension into femoral or popliteal vein but not considered to be a DVT and 1 patient had a DVT. High BMI and increasing length of the pre-operative junction was associated with lower incidence of flush occlusion; higher rates of flush occlusions were noted in patients undergoing short saphenous vein (SSV) EVLT (OR 4.11, 95% CI 2.34-7.20; P < .001). Conclusions: Consideration should be given to increase the intra-procedure laser tip junction to more than 2 cm particularly in patients undergoing SSV treatment to ensure that residual stump is sufficiently distal to SPJ and SFJ reducing risks of thrombus into the femoral or popliteal veins. Lower BMI may be associated with higher risk of this though the reasons for this are unclear.